1999
DOI: 10.1044/1058-0360.0803.273
|View full text |Cite
|
Sign up to set email alerts
|

Sentence Recast Use by Parents of Children With Typical Language and Children With Specific Language Impairment

Abstract: Many early studies failed to find differences in the language input of parents to children with specific language impairments (SLI) when compared to the input provided for MLU-matched children with typical language (TL). More recent investigations have revealed significant differences in the frequency of sentence recasts provided to young children. Specifically, parents of children with SLI have been shown to produce fewer recasts than do parents of younger children with TL. Because recasts have been shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…Analysis of data from individual studies has generally found that differing rates of recasts are associated with differing degrees of progress on proximal outcome measures (Hassink & Leonard, 2010, Girolametto et al, 1999) but that the relationship may be complex and change as the child becomes more proficient with a target structure (Fey et al 1993). Evidence suggests that targeting a rate of approximately 0.8 – 1 recast/minute may be beneficial (Camarata et al 1994; Fey et al, 1999). The results from Proctor Williams and Fey (2007) suggest that too high a rate may reduce efficacy as has been shown with typically developing children (Proctor Williams & Fey, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of data from individual studies has generally found that differing rates of recasts are associated with differing degrees of progress on proximal outcome measures (Hassink & Leonard, 2010, Girolametto et al, 1999) but that the relationship may be complex and change as the child becomes more proficient with a target structure (Fey et al 1993). Evidence suggests that targeting a rate of approximately 0.8 – 1 recast/minute may be beneficial (Camarata et al 1994; Fey et al, 1999). The results from Proctor Williams and Fey (2007) suggest that too high a rate may reduce efficacy as has been shown with typically developing children (Proctor Williams & Fey, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…A conversational recast is a response to a child's utterance in which the adult repeats some or all of the child's words and adds new information, while maintaining the basic meaning expressed by the child (Fey, Krulik, Loeb, & Proctor-Williams, 1999; Nelson, 1989). The additional information may be syntactic, semantic and/or phonological.…”
mentioning
confidence: 99%
“…Although parents of children with LI produce recasting at the same rate as parents of children with TL at the same level of language (Fey, Krulik, Loeb, & Proctor-Williams, 1999), this level of recasting was only correlated with subsequent language usage for children with TL and not for children with LI (Proctor-Williams et al, 2001). The density of exposure to grammatical features is also important.…”
Section: Dose Frequency Within Sessionsmentioning
confidence: 93%
“…Analysis of data from individual studies has generally found that differing rates of recasts are associated with differing degrees of progress on proximal outcome measures (Girolametto et al, 1999;Hassink & Leonard, 2010) but that the relationship may be complex and may change as the child becomes more proficient with a target structure (Fey et al, 1993). Evidence suggests that targeting a rate of approximately 0.8-1.0 recast/min may be beneficial (Camarata et al, 1994;Fey et al, 1999). The results from Proctor- Williams and Fey (2007) suggest that too high a rate may reduce efficacy, as has been shown with typically developing children.…”
Section: Effects Of Dosagementioning
confidence: 97%